Engineering cell penetrating peptides on ferritin cage for enhanced drug delivery. - Bhaskar Sathyamoorthy. (2013)
Delivering drugs into the cell environment has always been a major challenge for the pharmaceutical industry. The cellular membranes are selectively permeable and it offers resistance for the uptake of therapeutic molecules. Drug carrier proteins that have the ability to load and carry drugs typically have complex structures. The complexity of their structure reduces their ability to translocate across the lipid membranes. Current methods used for delivery of macromolecules such as viral vectors and cationic liposomes, lead to adverse effects like cytotoxicity and immunogenicity. Techniques such as electroporation and micro-injection can disrupt the membrane stability. To address this challenge, we develop model amphipathic cell penetrating peptides containing protein transduction domains, with the ability to penetrate the cell membranes in an energy independent non-endocytotic manner. They are short with less than 30 amino acids in length, positively charged and have alpha helical secondary structure. Efficient MAP peptides can serve as potential cell transfusion agents capable of delivering active molecules into malignant cells for therapeutic purposes. In this project, they are fused with drug loaded Archaeoglobus fulgidus ferritin (AfFtn-AA) cages and are hypothesized to aid the translocation these molecules across the membrane barrier. The cloning and production of the CPP-modified AfFtn-AA are optimized.